G-Weak Contraction in Ordered Cone Rectangular Metric Spaces. (27th May 2013) - Malhotra, S. K.; Sharma, J. B.; Shukla, Satish
Abstract : We prove some common fixed-point theorems for the ordered g -weak contractions in cone rectangular metric spaces without assuming the normality of cone. Our results generalize some recent results from cone metric and cone rectangular metric spaces into ordered cone rectangular metric spaces. Examples are provided which illustrate the results.